Environmental Pollution; Causes, effects and solutions - Gayatri Sunkad (Research Parks Publishers, 2021)
The environmental pollution is a burning issue before the contemporary world. The environmental pollution is not a major problem before humankind, even including the living beings, plant life and nature has to suffer due to the greediness of man. The environmental pollution is caused by the misusing exploiting the nature of man which has to suffer f even our next generation. Population explosion, highly industrialization, misusing the nature, irresponsible nature is the major reasons for the environmental pollution. The environmental pollution is having its own causes, effects which are horrible some times, but by having some remedial measures, we can decrease the level of environmental pollution, and by some judiciously acts, we can maintain the purify of mature.